(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of implementing quality management activities in hospitals based on Circular No. 19/2023/TT-BYT at selected public general hospitals in Hanoi City in 2024. Method: A cross-sectional descriptive study was conducted from April 2024 to October 2024 at eight grade-II public general hospitals under the Hanoi Department of Health. Data were collected using the templates specified in Circular No. 19/2013/TT-BYT. Quantitative data were analyzed using Redcap software. Results: All hospitals participating in this study fully implemented the 83 hospital quality management criteria. However, only 5 out of 8 hospitals had a comprehensive quality improvement plan. All hospitals developed tools to monitor key performance indicators and established regulations and procedures for medical incident reporting (MIR). Conclusion: The study revealed that the participating hospitals have relatively well implemented hospital quality management activities; however, certain criteria remain inadequately addressed.